Implementation of the Project for Strengthening the Pancasila Student Profile at Xaverius IV Elementary School and Xaverius V Elementary School Palembang - Utami, Tresiana Sari Diah; Indri, Bernadine Ajeng Indriasari (Journal of Education, Religious, and Instructions (JoERI), 2024)
The Independent Curriculum was developed in Indonesia based on the 2013 Curriculum. The Covid-19 pandemic has had a changing impact on the implementation of the 2013 Curriculum. The Independent Curriculum at Xaverius IV Elementary School and Xaverius V Elementary School Palembang has been implemented for two years. The Strengthening Pancasila Profile Project is a reflection of the implementation of the Independent Curriculum. This research aims to describe the implementation of the Pancasila Student Profile Strengthening Project which has been implemented at Xaverius IV Elementary School and Xaverius V Elementary School Palembang. This research approach is a qualitative research approach with descriptive methods. The research subjects were twenty-one educators at SD Xaverius IV and SD Xaverius V Palembang. Primary data collection techniques using questionnaires. The questionnaire was created with an open question type. Data analysis techniques refer to qualitative research data analysis techniques, namely data reduction, data identification, and drawing conclusions. The results of the research show that in implementing the Pancasila Student Profile Strengthening Project, educators at Xaverius IV Elementary School and Xaverius V Elementary School Palembang pay attention to several things, namely, paying attention to the selection of themes or topics, determining dimensions and elements, determining the concept of learning objective flow (ATP), and finally determining assessments and assessment rubrics.